Application of new wall, window, and lighting technology to a case study building - Balaka, Ridway; Surapong Chiraratananon; G.V. Dang; Supachart C.; Eastern Indonesia University Development project (EIUDPCIDA) (Bangkok : Asian Institute of Technology, 1993)
An efficient building design involves not only functional aspects with respect to structural and space utilization but also environmental aspects and energy considerations. The use of energy in the building can be optimized through a proper choice of the building components and a proper design of the building construction. This thesis work is focused on the building envelope in connection with the energy saving on the cooling load of the air-conditioning system and energy saving on the lighting system. The energy efficiency in lighting system in Thai Airways Building can be improved through the changing of luminaire system, through the proper design on illuminance distribution by employing task lighting concept, and through the use of daylighting. The use of coated glazing in Thai Airways Building can be improved if all of them are changed to be single clear glazing with the range of window to wall ratio between 0.1 and 0.275. The rest of the area of the window which is beyond the range of wwr used can be attached false wall (back up wall). The clear single glazing is the best energy performance at the range of wwr between 0.1 to 0.275. At the WWR greater than 0.3, Low-E glazing is the best performer in terms of energy savmg. The Low-E glazing has been proved as the best performance glazing in terms of total electric for cooling and lighting, however,the economic aspect has to be carefully weighted between infestation cost for installation and the energy saving cost. The C-B-F-G wall configuration has the best performance in terms of solar heat conduction while B-A-G has a very close performance to C-B-F-G configuration. However, the use of B-A-G configuration will be much more advantageous if the economic consideration is emphasized. The optimum WWR of these opaque wall is in between 0.1 and 0.2.
Thesis (M.Eng.) - Asian Institute of Technology, 1993
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering.
Keywords: Lighting